Leszek Kołakowski on Rationalism. Critical Analysis - Kleszcz, Ryszard (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
Leszek Kołakowski (1927–2009) was a thinker whose reflection was at the beginning associated with Marxism, anthropocentrism, anti-absolutism and a radically secular attitude. At the same time, from the very beginning Kołakowski, as a philosopher, was highly critical of the positivist version of rationalism. The paper presents and analyses the philosopher’s views on rationalism. This requires appropriate methodological analyses and the distinction between different types of rationalism. The presented analysis shows that the evolution of Kołakowski’s views means resignation from radical anthropocentrism and the slogans of fighting secularism. A thinker, retaining some elements of anti-absolutism and the related skepticism, positively valorises the content related to European culture and Christianity.